OPTIMIZING DELIVERY BALANCE IN MOTORCYCLE RIM DISTRIBUTION USING ODOO ERP: A CASE STUDY OF TWO-STEP WORKFLOW AND PULL/PUSH RULES AT CV. MORO DADI MAKMUR - Alexander Machicky Mayestino (Lembaga Penelitian dan Pengabdian Masyarakat / Narotama University Press, 2025)
This research explores the implementation of Odoo Enterprise Resource Planning (ERP) concepts to achieve effective balance control in motorcycle wheel rim (velg) deliveries at CV. Moro Dadi, an Indonesian Small and Medium Enterprise (SME) specializing in the distribution and supply of motorcycle components. The study emphasizes a two-step process involving the creation and execution of Manufacturing Orders (MOs) for semi-finished goods (quality inspection and preparation) and finished goods (final packaging and delivery), combined with the strategic configuration of Routes and Pull/Push Rules to optimize inventory flow, prevent stock imbalances (overstock or stockouts), and streamline the supply chain. A mixed-methods sequential explanatory design was employed within a single-case descriptive study framework. Quantitative data were derived from Odoo transaction logs and reports (delivery accuracy, balance ratios, error rates over 12 months), while qualitative insights came from semi-structured interviews, on-site observations, and document analysis with key stakeholders (production managers, warehouse staff, and ERP administrators). The implementation resulted in substantial operational improvements: the delivery balance ratio increased by approximately 12% (from 1.18 to 1.32), transaction and delivery discrepancies decreased by 82% through automation of transfer rules and real-time stock visibility, and overall, on-time delivery performance showed marked enhancement, particularly during peak demand periods. These gains stem from granular control enabled by the two-step workflow, automated replenishment triggers via Pull Rules, and optimized warehouse routing that directs rims through inspection, storage, picking, and shipping zones with minimal manual intervention. This study contributes to the body of knowledge on applied ERP adoption in resource constrained SMEs by demonstrating how open source Odoo can be tailored to address industry specific challenges in automotive component distribution namely maintaining balanced inventory and reliable delivery schedules. The proposed framework offers a replicable, cost effective model for similar SMEs in the motorcycle aftermarket sector to achieve greater supply chain agility, transparency, and competitiveness in Indonesia's growing two-wheeler market.